2006
DOI: 10.4315/0362-028x-69.9.2123
|View full text |Cite
|
Sign up to set email alerts
|

Daily Variability of Listeria Contamination Patterns in a Cold-Smoked Salmon Processing Operation

Abstract: An understanding of Listeria transmission and contamination patterns in processing environments of ready-to-eat foods is critical for improving control of Listeria monocytogenes. A cold-smoked fish processing operation was the site used to study variability in Listeria contamination in a processing environment associated with a ready-to-eat food product throughout one production week (five consecutive days). Intensive testing was conducted on finished products and environmental samples collected at the beginni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…However, approximately equal proportions of the two species were found in separate fish processing plants by Eklund et al (27) and Chen et al (15). Conversely, Hu et al (34) did not recover any L. innocua from 782 environmental and product samples taken from a cold-smoked fish processing facility. Further studies are needed to determine if the reported variation in proportions of L. monocytogenes to L. innocua is related to differential growth during the enrichment procedure or if nonpathogenic species of Listeria might affect growth and survival of L. monocytogenes in agricultural and food processing environments.…”
Section: Resultsmentioning
confidence: 93%
“…However, approximately equal proportions of the two species were found in separate fish processing plants by Eklund et al (27) and Chen et al (15). Conversely, Hu et al (34) did not recover any L. innocua from 782 environmental and product samples taken from a cold-smoked fish processing facility. Further studies are needed to determine if the reported variation in proportions of L. monocytogenes to L. innocua is related to differential growth during the enrichment procedure or if nonpathogenic species of Listeria might affect growth and survival of L. monocytogenes in agricultural and food processing environments.…”
Section: Resultsmentioning
confidence: 93%
“…3 L. monocytogenes is ubiquitous in nature; thus, it is commonly isolated from farms and food processing facilities. [5][6][7][8][9][10] Since L. monocytogenes has the ability to grow and persist at refrigeration temperatures, 11,12 even a small quantity of the bacteria is a potential food safety concern. The L. monocytogenes that is attached to food processing surfaces is one source of the Listerial contamination in processed food products, especially ready-to-eat foods such as cheese, meat, and poultry.…”
Section: Introductionmentioning
confidence: 99%
“…Thus contamination of RTE foods in processing plants is likely to be a stronger risk factor for human exposure than contamination closer to consumption (e.g., in household kitchens). Consequently, understanding and reducing contamination in food processing plant environments has been a focus for many years (Cox et al, 1989;Hu et al, 2006;Samelis and Metaxopoulos, 1999), while contamination in retail environments has only been addressed more recently (Sauders et al, 2004).…”
Section: Monocytogenes In Food Processing Plantsmentioning
confidence: 99%